2011
DOI: 10.1039/c0jm04385k
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linked membranes with a macromolecular cross-linker for direct methanol fuel cells

Abstract: With the goal of reducing water swelling and methanol permeability in sulfonated proton exchange membranes (PEM), bromomethylated poly(ether ether ketone) was synthesized and used as a macromolecular cross-linker. The cross-linking reaction was performed at 195 C for 5 h and resulted in cross-linked membranes with high cross-linked density. Compared to the pristine membrane, the cross-linked membranes displayed greatly reduced water uptake and methanol permeability. Other properties of the cross-linked membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…An in-depth theoretical analysis suggested that higher acid content does not always result in higher proton conductivity [135]. In addition, the degree of crosslinking plays an important role in optimized properties of SAP and should be carefully controlled and optimized [71,109]. A too small degree of crosslinking is not sufficient to maintain the desired dimensional, mechanical and thermal stability of high IEC SAP.…”
Section: Crosslinked Sap By -So 2 -Bridgesmentioning
confidence: 97%
See 2 more Smart Citations
“…An in-depth theoretical analysis suggested that higher acid content does not always result in higher proton conductivity [135]. In addition, the degree of crosslinking plays an important role in optimized properties of SAP and should be carefully controlled and optimized [71,109]. A too small degree of crosslinking is not sufficient to maintain the desired dimensional, mechanical and thermal stability of high IEC SAP.…”
Section: Crosslinked Sap By -So 2 -Bridgesmentioning
confidence: 97%
“…Other kinds of XL reactions based on pseudo Friedel-Crafts alkylation were reported: the crosslinking reaction occurred between benzylic alcohol and a phenyl ring linked to phosphazene backbone [108] or bromomethylated SPEEK [109] under acidic or heating conditions. XL SPEEK with bromomethyl groups shows water uptake, methanol permeability and proton conductivity reduced with respect to those of pristine SPEEK, but the thermal stability was also unexpectedly slightly lower due to remaining CBr bonds after crosslinking.…”
Section: Crosslinked Sap Via Friedel-crafts Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…comparison with a macromolecular crosslinker [21], but the later was seldom reported in the field of AEMs.…”
Section: Introductionmentioning
confidence: 98%
“…S1. Compared with pristine SPI, the Young's modulus of SPI‐cPNIPAm semi‐IPN membranes increases after the incorporation of semi‐IPN cPNIPAm networks, while the tensile strength and elongation at break are decreased because of the crosslinking structure which results in a decline of elasticity of the semi‐IPN membranes . However, the modulus of SPI‐25‐cPNIPAm is obviously reduced due to the phase separation between SPI and cPNIPAm.…”
Section: Resultsmentioning
confidence: 99%